EFEKTIVITAS METODE MELATIH MENGGUNAKAN ALAT BANTU PELAMPUNG DAN TANPA ALAT BANTU PELAMPUNG TERHADAP KECEPATAN RENANG GAYA BEBAS 5O METER - Firta suli, Risma Ananda; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
Abstract This study aims to determine the effectiveness of the training method using a buoy and without a buoy on the 50 meter freestyle swimming speed. This study used an experimental method with a